'The honour of the righteous will be restored' : Psalm 75 in its social context - Botha, Phil J. (Old Testament Essays, 2002)
Psalm 75 is often assumed to be a psalm of thanksgiving. Others regard it as part of a cultic liturgy celebrating God's judgement on evildoers. But few researchers have recognised the important role played by the social values of honour and shame in the psalm. It is argued in this paper that it is not possible to understand the text as an instrument of communication if the social context is not taken into consideration. The psalm is analysed on a poetic and a social-critical plane. It seems that the purpose of this text was to confirm the belief of a group of Israelites in the power and willingness of Yahweh to intervene on their behalf. As such it also constitutes a prayer that the national honour of this group of believers will be restored.
free